Using Modified Multi-Walled Carbon Nanotubes with Ultrasonic Homogenizer for BTEX Removal from Aqueous Solutions - Pourzamani 1, Hamidreza; Parseh 2, Iman; Hadei 3, Mostafa; Rashidashmag‌h 4, Fatemeh; Darvish 1, Mohammad; Fadaei 1*, Saed (Shahroud Journal of Medical Sciences, 2019)
Background: BTEX refers to a volatile compound with single aromatic ring in petroleum including benzene, toluene, ethyl benzene, and xylenes. Due to its flammability, toxicity and carcinogenicity properties, BTEX has many adverse effects on human health. This study aimed to evaluate the efficiency of multi-walled carbon nanotube (MWCNT) modified with an ultrasonic homogenizer (UH) to remove BTEX from aqueous solutions.Methods: MWCNT was modified in different concentrations, times and intensities. Then, the best condition was selected. After modification based on the design of experiments (DOE), 16 experiments were arranged at 4 levels with 4 factors. Samples required for simulation were built according to the standard methods and then analyzed by gas chromatography mass.Results: The results revealed that the optimum conditions for modified carbon nanotubes were obtained at concentration of 30% sodium hypochlorite, time of 5 seconds, and intensity of 50 dB. The optimum conditions for initial BTEX concentration, MWCNT dose, contact time, and pH were 100 mg/L, 2000 mg/L, 20 min and 7 respectively.Conclusions: The results indicated that carbon nanotubes modified with homogenizer are a simple and effective technique to remove BTEX from the environment.